Analysis of Borepile Foundation Bearing Capacity in Building Construction Projects with Pile Driving Analyzer Test - Muhammad Hafizh Prasetyo; Fazry Hidayat; Hardian Tri Guntoro; Ingrid Multi Rezeki (Interdiciplinary Journal and Hummanity (INJURITY), 2025)
In the construction process, a building requires good planning, because structural elements must be able to receive loads in the form of axial directional loads such as gravitational loads as well as lateral directional loads such as wind loads and earthquake loads, all of which will later be passed on to the lower structure, namely the foundation. One of the things that is reviewed from the foundation is the value of the carrying capacity, to find out the value of the carrying capacity of a foundation can be calculated theoretically based on data from soil investigations in the field. Meanwhile, the Pile Driving Analyzer (PDA) is used to verify the results of the calculation. This study aims to calculate and analyze the bearing capacity of the foundation compared to the results of PDA. The method used is the Schmertmann & Nottingham method as well as the Mayerhoff method. The results of this study are carrying capacity using the Schmertmann & Nottingham method based on the results of the sondir test at the S1 point obtained a result of 804.15 tons, at the S2 sondir point the result was 761.99 tons, the S3 sondir point was 823.45 tons and at the S4 sondir point of 841.68 tons. The carrying capacity using the Meyerhoff method based on the results of the sondir test at the S1 point obtained a result of 572.39 tons, the S2 sondir point was 568.93 tons, the S3 sondir point was 568.84, and the S4 sondir point was 562.4 tons. The largest ultimate bearing capacity (Qu) value is obtained from the Schmertmann & Nottingham method at the sondir point S4, The smallest ultimate bearing capacity (Qu) value is obtained from the Meyerhoff method at the sondir point S4. The calculation results that show the least difference and are closest to the PDA are using the Meyerhoff method at the S4 sondir point and the BP-109 PDA with a difference of 115.5 tons. The Schmertmann & Nottingham method shows much greater results than PDA calculations